The History of the Origins of Korong Kampuang and Settlement Patterns in Nagari Panti Selatan, Panti District, Pasaman Regency - Ina Helena Agustina; Imam Indratno; M. Ari Fandi (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2025)
This study aims to describe the settlement patterns in Nagari Panti Selatan, a region in West Sumatra, influenced by its history, Minangkabau adat culture, and social interactions within the community. Using a descriptive qualitative approach with phenomenology, the research gathered data through interviews with adat leaders and field observations. The findings indicate that the settlement pattern in Nagari Panti Selatan was formed based on land clearing by adat leaders known as tiang pancang nan ampek and influenced by the matrilineal adat system and the division of adat territories. The settlement pattern in this Nagari is generally clustered (baumpuak), following the strong principles of mutual cooperation and togetherness in the community. Some areas, such as Tambangan, Petok, and Ujuang Padang, show clustered settlement patterns, while newly developed areas are more influenced by access to main roads. The study also emphasizes the importance of preserving adat values and culture in the development of Nagari Panti Selatan. In conclusion, although settlement patterns have changed with the development of infrastructure, adat values still play a dominant role in regulating social life in Nagari Panti Selatan. The study suggests the importance of preserving the history of adat and strengthening the role of adat leaders in development planning to maintain the balance between tradition and modernization.